Prevalence of disordered eating: A comparison of male and female collegiate athletes and nonathletes - DiPasquale, L. D.; Petrie, T. A. (Journal of Clinical Sport Psychology, 2013)
Eating disorder prevalence rates among athletes vary greatly because of the different ways in which researchers have measured and classified them, and the extent to which they are higher than those found among nonathletes remains unresolved. The present study examined prevalence of eating disorders, body image issues, and weight control behaviors using a valid diagnostic measure. Participants included 146 male and 156 female NCAA Division I student-athletes and a matched sample of 170 male and 353 female collegiate nonathletes. Overall, eating disorder prevalence rates and use of pathogenic weight control behaviors were lower among nonathletes than athletes. Rates for athletes in the current study were lower than previous studies. These findings are likely due to the lack of anonymity the athletes had when completing questionnaires, as data were collected through athletes` preseason physicals, whereas nonathletes completed questionnaires anonymously over the Internet. Recommendations for athletic departments` screening for eating disorders are made.